JSE 31:4 Editorial - Braude, Stephen (Journal of Scientific Exploration, 2017)
Although this issue of the JSE, as usual, contains a diverse cocktail of interesting papers, two of those papers are sufficiently out of the ordinary to deserve a few comments. In this issue, we fearlessly address—for the second time in the JSE’s history—one of the thorniest and most interesting topics in English literature—namely, the debate over Shakespeare authorship. As some current SSE members are undoubtedly aware, many have challenged the orthodox view that the works of Shakespeare were written by the person traditionally identified as the author—that is, William Shaxpere of Stratford-upon-Avon. SSE stalwart (and my editorial predecessor) Peter Sturrock tackled the topic in the JSE in 2008 (Sturrock 2008), and then several years later followed that up with a book on the subject (Sturrock 2013). What Sturrock did brilliantly was to demonstrate how one can invoke Bayesian probability theory to challenge the orthodoxy in a compelling way. For this issue, we reprint that paper and combine it with a penetrating new work on the subject by David Roper. Roper approaches the matter from a different angle than that adopted by Sturrock. He draws on the science of cryptography to argue that the true author of the Shakespeare works was Edward de Vere, the 17th Earl of Oxford. (This is also the conclusion emerging most naturally from Sturrock’s book.) Roper argues that Sixteenth-Century techniques of using codes and ciphers were both common and quite well-developed, and that these permitted concealing secret messages within apparently innocent passages of prose or poetry. Moreover, Roper marshals a great deal of historical evidence for the claim that de Vere and others had good reason to conceal de Vere’s authorship of the works attributed to Shaxpere. So I hope our readers will enjoy this excursion into what should be largely unfamiliar territory for most of them. I know I learned a great deal from these papers, and I’m pleased that the JSE can make a scientific contribution to this venerable debate. As I see it, the papers by Sturrock and Roper together constitute a fascinating and impressive full frontal assault on the orthodox view.